High-performance MWCNT/graphene nano-enhance phase change materials for efficient thermal energy storage - Mohd Arif Fikri, Rosli (2023)
Thermal Energy Storage (TES) using Phase Change Materials (PCMs) has garnered substantial interest among scientists around the globe due to their potential as an efficient energy storage medium. PCM offers a solution with good phase-change characteristics, small temperature variation during charging or discharging cycles, and higher energy storage densities. However, PCMs suffer from low thermal conductivity. The addition of nanoparticles has been proven to enhance the thermophysical characteristics of base materials and this formulation is known as Nano-enhanced Phase Change Material (NePCM). NePCM exhibits quicker storing and releasing rate during the phase transition process. Even though the behaviour of the PCMs improved by adding nanoparticles, they also resulted in several drawbacks. The major drawbacks are sedimentation and agglomeration when the composite transforms into a liquid state. Incorporating Carbon-based nanoparticles (CBNP) into PCM for TES systems is an underexplored option. Furthermore, sedimentation and agglomeration of CBNP in PCMs are critical problems that must be overcome before their effective use as passive thermal energy storage media in industrial or everyday applications. Therefore, surface modification of the CBNP might be beneficial in reducing sedimentation and agglomeration in PCMs for effective TES applications. As such, the main objective of the present work is to formulate, functionalize, and characterize the Carbon-based NePCM for efficient thermal energy storage. These objectives are achieved by surface modification of CBNP using surfactants and functionalization methods (covalent and non-covalent approaches). The formulated materials later undergo various characterizations to investigate various properties and their performances. The present study explores the effect of multi-walled carbon nanotube (MWCNT) weight percentage (0–1.0 wt%) and Graphene nanoplatelets (GNP) with 2 surface modifications which are surfactants addition (Sodium Docecylbenzene Sulfonate (SDBS)) and functionalization (Carboxyl group: -COOH) on the thermal conductivity, melting temperature, melting latent heat and thermal stability of Paraffin Wax (PW) PLUSICE A70. The PLUSICE A70 will be melted and CBNP (MWCNT & GNP) will be sonicated inside the mixture. Beside that, the step are being repeated with the presence of surfactant and functionalization inside the NePCMs. It is found that the maximum thermal conductivity is 0.498 W/m.K (109.452%) exhibited by A70/1.0wt% MWCNT, and for GNP, AG-1.0 showed 0.354 W/m.K, which is 48.83% compared to pure A70. By adding SDBS as a surfactant, ASMW-1.0 produced 0.536 W/m.K, 125.078% higher than pristine A70, and ASG-1.0 indicated 0.529 W/m.K (122.26%). Attaching the Carboxyl group at the surface of CBNP, makes the nanocomposite of AFMW-1.0 produce the highest thermal conductivity enhancement, 0.597 W/m.K (150.748%), and for GNP, AFG-1.0 showed 0.573 W/m.K (140.88%). The Differential Scanning Calorimetry (DSC) results revealed that the minimum decrement latent heat by -1.74% for 1.0 wt% FMWCNT/A70 (AFMW-1.0) and for maximum decrement, -6.86% for 1.0 wt% SGNP/A70 (ASG-1.0) respectively. Light transmittance of ASMW-1.0 reduced to 98.47% more than pure PW PCM. Furthermore, there is no sufficient change in the thermophysical and chemical stability of all materials after undergoing thermal cycles. The best nanocomposites will lead to bridging the current gaps in the research and recommend future work on developing new PCMs and NePCMs integrated in TES systems to improve performance, and longer life, thus adding to the environmental benefits of realized gradual improvement.